Optimization of the VITROCELL® Exposure System for In Vitro Toxicity Testing of Diesel Emissions at the Air-Liquid Interface - Greenan, Rebecca (Université d'Ottawa / University of Ottawa, 2015)
Relative to traditional methods, air-liquid interface (ALI) exposures constitute a superior in vitro model for assessing the toxicological activity of complex aerosols. By removing the medium barrier, aerosols can be delivered to the cells at their apical surface. This project investigated the utility of the commercially available VITROCELL® exposure system for comparative toxicological assessment of complex aerosols (freshly-generated diluted diesel exhaust and simulated urban smog). The system setup was modified to improve control of aerosol properties (temperature and humidity) and cellular responses (dynamic range). Following optimization, cytotoxicity (WST-1 and LDH assays) and expression of selected genes involved in proinflammatory signalling and oxidative stress responses (via quantitative RT-PCR) were quantified following 1 hour aerosol exposures. The results showed only limited, variable responses following exposures to high concentrations of diesel exhaust. Lack of consistent and robust responses are likely due to poor deposition of particulate matter from the test aerosols.
Keywords: Toxicology; Air-liquid interface; Diesel; Aerosol; A549; BEAS-2B; VITROCELL; Engine; In vitro; Particulate; Environment; Health; Methods development; Urban air; Smog; Nitrogen dioxide